Culture and Sensitivity Pattern of Urinary Tract Infection in Hospitalized Children in Patan Hospital - Amatya, Puja; Joshi, Suchita; Shrestha, Shrijana (Journal of Nepal Paediatric Society, 2016)
Introduction: Urinary tract infection is one of the most common infections in children. Antibiotics are usually given empirically before urine culture reports are available. The primary aim of this study was to see the causative organisms and culture and sensitivity pattern of urinary tract infection in hospitalized children. Material and Methods: All children aged 0-15 years with culture positive urinary tract infections who were admitted to children’s ward from 14th April 2013 to 14th April 2014 were included. The causative organisms for urinary tract infection along with its antibiotic sensitivity pattern were retrospectively reviewed and analyzed. Results: 48 cases of culture positive urinary tract infection were enrolled in this study in a period of 12 months. The most common causative organism was Escherichia coli (67%), followed by Klebsiella pneumoniae (21%), Non-hemolytics streptococcus (4%), Enterobacter (2%), Acinetobacter (2%), Proteus (2%) and Coagulase negative staphylococcus (2%). Most cases of the culture positive urinary tract infection occurred between 2 months to 1 year of age. Out of 48 cases, 90% were sensitive to Amikacin and 85% were resistant to Ofloxacin. Conclusion: Escherichia coli is the most common organism causing urinary tract infection in children. As resistant to first line antibiotic is increasing, antibiotic stewardship programme should be strengthened. J Nepal Paediatr Soc 2016;36(1):28-33